Justice in Islamic Criminal Law: Study of the Concept and Meaning of Justice in The Law of Qiṣāṣ - Muhammad Tahmid Nur (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: Contextualizing the justice dimension in the law of qiṣāṣ has a humanitarian basis, so it needs to be understood under the context and development of current law. This endeavor is necessary to have a more thorough and contextual understanding of the esoteric meaning of qiṣāṣ legal justice. This article examines the contextualization of the meaning of justice in the construction of qiṣāṣ law to further elaborate on its human values, using a normative approach with philosophical analysis. This study data consisted of primary and secondary data. Based on the study analysis, it can be concluded in three points. First, the meaning of justice in Islamic law is oriented to realizing human benefit based on humanity and religious values. Justice in recompense punishment is found in the guarantee of life from God as the Lawgiver. Second, the implementation of qiṣāṣ punishment always prioritizes respect for the perpetrators' and victims' rights. This is a form of respect for human values. Third, in terms of applying punishment, the construction of qiṣāṣ law allows flexibility by contextualizing the meaning of justice to be adapted and applied in society.Abstraks: Kontekstualisasi dimensi keadilan dalam hukum qiṣāṣ pada dasarnya memiliki basis kemanusiaan sehingga ia perlu dipahami sesuai dengan konteks dan perkembangan hukum kontemporer. Upaya ini penting dilakukan agar bisa memahami makna esoteris keadilan hukum qiṣāṣ lebih komprehensif dan kontekstual. Artikel ini mengkaji kontekstualisasi makna keadilan dalam konstruksi hukum qiṣāṣ guna mengelaborasi lebih lanjut nilai-nilai kemanusiaan yang ada di dalamnya. Penelitian ini menggunakan pendekatan normatif dengan analisis filosofis. Data-data dalam penelitian ini terdiri atas data primer dan sekunder. Berdasar kajian dan analisis yang telah dilakkan, diperoleh simpulan bahwa: pertama, makna keadilan dalam hukum Islam diorientasikan pada terwujudnya kemaslahatan manusia yang berlandasakan nilai kemanusiaan dan ketuhanan. Keadilan dalam hukuman pembalasan yang setimpal terdapat pada jaminan garansi kehidupan dari Tuhan sebagai Pembuat Hukum. Kedua, pelaksanaan hukuman qiṣāṣ selalu mengedepankan prinsip penghormatan atas hak individual pelaku dan juga keluarga korban. Hal ini merupakan wujud penghargaan terhadap nilai kemanusiaan. Ketiga, dari sisi penerapan hukumannya, konstruksi hukum qiṣāṣ memungkinkan untuk diterapkan secara fleksibel dengan mengontekstualiasikan makna keadilan untuk bisa diadaptasikan dan diterapkan di masyarakat.